Vocational education and training in the UK. Strategies to overcome skill gaps in the workforce - Page, Rosie; Hillage, Jim (Berlin, 2006)
"This paper presents an overview of recent literature concerning skill gaps and vocational training in the UK. There is considerable employer influence in the market-led UK training system and the government typically encourages employer-funded training via policy and through the institutional and qualification frameworks. This approach is in contrast to much of the training policy across Europe. Employers in the UK train for a variety of reasons, primarily led by business needs. There are distinct patterns of who receives employer-funded training, and how intensive any training received is. This is linked to the prioritisation of the training, within a limited budget, to best meet business needs and which is likely to lead to the largest return on investment via benefits such as increased productivity. The UK training system faces a number of challenges in the future, including an ageing workforce, trying to increase the take-up and quality of vocational training and breaking the low skills, low quality cycle resulting from businesses competing on cost."